2010
DOI: 10.3109/15368371003627290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the “zero” Magnetic Field on Early Embryogenesis in Mice

Abstract: It was shown that the 250-fold screening of the geomagnetic field (GMF) ("zero" magnetic field with an induction of 0.2 muT) affects early embryogenesis and the reproduction capacity of mice in vivo. Pregnant NMRI mice at the zygote stage placed in this "zero" magnetic field (MF) lost the ability to bear offspring babies although their embryos developed up to the blastocyst stage without any visible deviations from the norm. The abortion of development in the "zero" MF occurred after the exit of the blastocyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…It has been established that eliminating the local GMF, that is, a hypomagnetic field (HMF), interferes with many aspects of living organisms. Animal experiments have shown that HMF exposure has adverse effects on embryonic development (inhibits early embryogenesis and reproduction capacity) and brain functions (makes memory ability and stability significantly worse) [Wang et al, ; Osipenko et al, ; Fesenko et al, ]. Continuous HMF exposure leads to increased abnormality in newts and Xenopus laevis (somatic defects, retarded, or blocked development) [Asashima et al, ; Asashima et al, ; Mo et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that eliminating the local GMF, that is, a hypomagnetic field (HMF), interferes with many aspects of living organisms. Animal experiments have shown that HMF exposure has adverse effects on embryonic development (inhibits early embryogenesis and reproduction capacity) and brain functions (makes memory ability and stability significantly worse) [Wang et al, ; Osipenko et al, ; Fesenko et al, ]. Continuous HMF exposure leads to increased abnormality in newts and Xenopus laevis (somatic defects, retarded, or blocked development) [Asashima et al, ; Asashima et al, ; Mo et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that that a GMF-shielded condition, so called a hypomagnetic field (HMF) (Mo et al, 2012), adversely affect many aspects of the living system, e.g. embryonic development (Mo et al, 2012; Wan et al, 2014; Osipenko et al, 2008; Fesenko et al, 2010), animal behaviors (Bliss and Heppner, 1976; Prato et al, 2005; Zamoshchina et al, 2012; Mo et al, 2015), and brain function (Zhang et al, 2004; Xiao et al, 2009; Binhi and Sarimov, 2009). Human subjects with short-term exposure to the HMF exhibited enlarged pupil size, increased the number of errors and the task processing time (Binhi and Sarimov, 2009, 2013) and increases capillary circulation and reduction of heart rate (Gurfinkel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the HMF exposure has been found to cause abnormal cognitive behaviors and disrupt embryonic development (Wang et al 2002; Zhang et al 2004; Asashima and Shimada 1991; Mo et al 2012b; Fesenko et al 2010), but the potential biological mechanism is rarely been investigated. The proliferation, differentiation, and quiescence of NPCs/NSCs are under strict control and kept in delicate balance in embryonic as well as in adult brains (Simons and Clevers 2011; Stine and Matunis 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Crys would probably acting as an important molecule in the sensation of the elimination of the GMF under the dark condition such as in a cell incubator. Accumulating evidence has shown that cells and tissues incubated in the HMF exhibited observable cellular responses which were light-independent (Fesenko et al 2010; Mo et al 2013; Martino and Castello 2011; Fu et al 2016; Martino et al 2010; Mo et al 2016). Our previous study has screened HMF-responding genes from neuroblastoma cells and verified that Cry2 was significant up-regulated after an 18 h short-term HMF exposure and down-regulated after a 48 h continuous HMF exposure (Mo et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation